Design and Development of User-friendly Computing Tool for Path Coefficient Analysis with Application to Mung Bean (Vigna Radiate L. Wilczek) Traits Towards Seed Yield - Muhammad Amin (Science Faculty of Chiang Mai University, 2019)
The contribution of causal traits/variables with targeted effect variable directly and indirectly, through other variables has always remained a course of concern for researchers. User-friendly computer programs, in relation to path coefficient analysis, are a major hurdle in finding direct and indirect causes of association. Thisuser-friendly computer program through path coefficient analysis method is used for the selection of significant traits contributing towards seed yield in Mung bean crop with eighteen, morphological and yield associated traits. Results reveal that harvest index, dry weight of biomass, fresh weight of biomass, seeds/pod, 1000-seeds weight and pods/plant are highly significant characters towards seed yield while pod length has a significant effect on the response variable. Path analysis shows that harvest index and dry weight of biomass have positive direct effect on seed yield. Based on the results obtained, it can be concluded that high yield of Mung bean crop could be obtained by selecting the breeding materials with the important traits on seed yield.